Good Corporate Governance dan Kinerja Keuangan: Bukti Empiris dari Sektor Perbankan Indonesia - Nasirwan, Nasirwan; Ridha, M. Arsyadi; Situngkir, Gomgom; Kholis, Azizul; Habibi, Muhammad Ridha (Universitas Negeri Padang, 2025)
This study aims to examine the effect of good corporate governance mechanisms on financial performance in banks listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022. The study population includes all banks listed on the IDX during that period, totaling 47 companies. Through purposive sampling, 21 banks were selected as the research sample. The data used were secondary data obtained from company financial reports accessed through the official website www.idx.co.id. Data analysis was performed using multiple regression with the assistance of EViews 13 software. The results of the study indicate that the board of commissioners and the audit committee do not have a significant effect on financial performance. Meanwhile, managerial ownership and institutional ownership were found to have a significant influence on the financial performance of banking companies. These findings broaden our understanding of how the institutional and structural context of Indonesian banking influences the substantive role of GCG. Practically, these findings provide implications for regulators and financial authorities to reevaluate the effectiveness of normative governance policies and encourage banks to improve the quality of GCG implementation more strategically, rather than simply as a form of formal compliance.